Gestão em SST: mapeamento sistemático de literatura com foco na construção civil - Philippsen Jr., Luiz; Weber, Adriana Santos; Weber, Ismael (SIMPÓSIO BRASILEIRO DE GESTÃO E ECONOMIA DA CONSTRUÇÃO, 2021)
Safety and health aspects are part of the strategic planning of contemporary organizations. These aspects must be observed and implemented in the day-to-day work and in all the products and goods developed by the organizations. The construction industry, as part of this contemporary organizational reality, increasingly adopts related practices to improve safety at the construction site. However, unlike traditional industrial sectors, the construction industry has specificities that also take it systematically among the most dangerous industrial sectors to work. This article presents an analysis of the scientific production on occupational safety and health management – OSHM, with focus on civil construction, specifically at the construction sites level. Throughout a systematic mapping study protocol, 108 published researches were collected by Web of Science. Using software and tools for bibliometric analyses, this article shows the main researches, authors, countries and institutions of research, the publication and dissemination platforms and the possible relations between the researches, researchers and subjects.